Selected Analytical Techniques of Solid State, Structure Identification, and Dissolution Testing in Drug Life Cycle Analytical Techniques in Drug Life Cycle - Kratochvíl, Bohumil (Masaryk University Press, 2023)
The textbook provides an overview of the main techniques applied in pharmaceutical industry, with the focus on solid-state analysis. It discusses spectral methods, thermal analysis, and dissolution testing, explains the theoretical background for each method and shows practical examples from a real-life drug-design and quality control applications. The textbook is thus intended for both pharmacy students and early career professionals.